STUDY OF EFFECT OF FRONT RAKE ANGLE AND BACK CLEARANCE ANGLE ABOUT CUT ABILITY CHARACTERISTICS OF SANDSTONE AND LIMESTONE USING DRAG PICK - ISMAIL HM SUFRIE (NIM : 121 06 039); Pembimbing : Dr. Ir. Suseno Kramadibrata, M.Sc.
Continuous mining system is one of the mining systems that continue to develop as the mining technology does. Continuous mining system uses drag pick in its cutting process, thus choosing the appropriate drag pick is important. In addition, material characteristics must be defined specifically to choose the right drag pick to use. This researchÃ‚Â’s purpose is to define effect front rake angle (α) and back clearance angle (β) on cut ability characteristics of sandstone and limestone. This research using three variations front rake angle (α) and back clearance angle (β), its variation as follows. - α=10o and β=20o - α=15o and β=15o - α=20o and β=10o One thing that is important in this research is to define specific energy of both sandstone and limestone using three variations of front rake angle (α) and back clearance angle (β). Rock characteristics can be determined by measuring its UCS and its ultrasonic velocity. Greater points of both parameters mean that the rock has bigger specific energy. This research show the result that test rock using variation α=10o and β=20o has smaller specific energy than two of them. Its mean that drag pick using variation α=10o and β=20o is more optimum to excavation. Limestone has bigger specific energy than sandstone.